Some aspects of analysis of the Ukrainian legislation regulating the production of veterinary medicines - I. V. Bushuieva; K. V. Petrova; Zh. M. Polova (Zaporozhye State Medical University, 2021)
The aim of the work was to study the current state of domestic legislation of state regulation in the field of licensing the activities of business entities manufacturing veterinary medicinal products and its harmonization with the requirements of the European Union. Materials and methods. The research materials were regulatory and legislative acts, regulations and principles of the state policy of Ukraine connected with licensing the activities of business entities manufacturing veterinary medicinal products, in force from 2015 to the present. To carry out this study, the methods of information retrieval, systematization, analytics, graphic, comparison, and data generalization were used. Results. The article presents the main results of the analysis of the Ukrainian legislation which regulates the production of veterinary medicines and preparations. According to the results of the analysis, it was found that in the period from 2015 to 2018, Ukrainian manufacturers of veterinary medicinal products worked in such conditions that did not require a license for this type of activity. By the decree of the President of Ukraine, the program of sustainable strategic development of the country "Ukraine-2020" was approved which provided for reforms in the format of deregulation and the development of entrepreneurship and excluded the necessity of licenses for veterinary drugs production. Conclusions. Based on the study, it can be concluded that the Law of Ukraine "On Licensing of Types of Economic Activities" dated March 3, 2015 No. 222-VIII was actually aimed at reducing the governmental influence and regulatory pressure on the activities of business entities involved in the production of veterinary medicinal preparations.